MEMPREDIKSI LAMA RAWAT PASIEN STROKE HEMORAGIK DENGAN EARLY WARNING SCORE (EWS) - Ika Subekti Wulandari; Erma Lina Yuniarti; Martina Eka Cahyaningtyas (STIKes Surya Global Yogyakarta, 2021)
Background of Study: Stroke according to World Health Organization (WHO) a clinical sign that develops fast due to focal or global brain function disorder marked by simptoms, last factor for more than 24 hours, can lead to death, and is caused by vascular disorder. The assessment of stroke status deterioration can also be seen from the assessment of Early warning Score (EWS). The hemorrhagic stroke patients treated at EWS wards are always put in the first priority as to anticipate a sudden stroke status deterioration so that the patient’s conditions stays stable and minimize the length of hospitalization. The Objective of this research is to investigate the correlation between early warning score and length of hospitalization of hemorrhagic stroke pattients at Kasih Ibu Hospital of Surakarta. Methods : Thia research used the quantitative descriptive correlational research method with cross sectional approach. Its population was all of the hemorrhagic stroke patients as many as 40 at Kasih Ibu Hospital of Surakarta. Purposive sampling was used to determine its samples. They consisted of 36 respondent. The data of the research were analyzed by using the Spearman’s Rank-Order Correlations. Results : The result of the analysis shows that the p value was 0.000 meaning that the early warning score had a correlation with the length of hospitalization of hemorrhagic stroke patients at Kasih Ibu Hospital of Surakarta. The result of this research can be a reference for hospital to arrange Standart Operational Procedure and assessment of EWS which is mandatorily perfomed at inpatient wards.Conclusion : EWS can be used as an indicator to determine the length of stay. for hemorrhagic stroke patients.Keywords : EWS, Lenght of Stay, hemorrhagic stroke